2014
DOI: 10.1111/odi.12270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of salivary function in patients with burning mouth syndrome

Abstract: OBJECTIVES: To investigate salivary function in patients with primary burning mouth syndrome (BMS) compared with control and to evaluate salivary hypofunction using salivary gland scintigraphy (SGS). METHODS: A total of 33 patients with primary BMS and 30 control subjects were enrolled in our study. The severity of the pain and the burning sensation on a 10-cm visual analog scale (VAS) and the Oral Health Impact Profile-14 (OHIP-14) were assessed. Unstimulated and stimulated salivary flow rates (SFRs) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 32 publications
6
40
1
Order By: Relevance
“…Although many BMS patients complain the feeling of dry mouth, most of the studies have shown that the salivary flow rate in BMS patients is the same as in controls (Hershkovich and Nagler, 2004;Granot and Nagler, 2005;de Moura et al, 2007). However, recently, in contrast to Boras et al (2010), Lee et al (2015) and Poon et al (2014) reported decreased unstimulated salivary flow rates in primary BMS patients compared to those of healthy controls, however, without any differences in stimulated salivary flow rates.…”
Section: Hyposalivation and Xerostomiamentioning
confidence: 95%
“…Although many BMS patients complain the feeling of dry mouth, most of the studies have shown that the salivary flow rate in BMS patients is the same as in controls (Hershkovich and Nagler, 2004;Granot and Nagler, 2005;de Moura et al, 2007). However, recently, in contrast to Boras et al (2010), Lee et al (2015) and Poon et al (2014) reported decreased unstimulated salivary flow rates in primary BMS patients compared to those of healthy controls, however, without any differences in stimulated salivary flow rates.…”
Section: Hyposalivation and Xerostomiamentioning
confidence: 95%
“…The attempt to treat xerostomia with urea 10% topically failed to improve saliva flow and taste, olfactory, and somesthetic thresholds 40 . Unstimulated saliva flow rates were shown to drop significantly only in BMS patients [41][42][43] , though scintillography of salivary glands did not evince any functional loss in either healthy or hyposalivation patients 41 .…”
Section: Saliva Changesmentioning
confidence: 88%
“…For many individuals, however, this dryness is perceived rather than actual 146148 . Interestingly, some studies show that unstimulated salivary flow is decreased in BMS patients, while stimulated flow is normal 149151 . As a corollary to these studies, patients with BMS do not have a higher caries index than healthy controls, suggesting that most of these individuals maintain salivary flow that is adequate for caries prevention 10 .…”
Section: Burning Mouth Syndrome (Bms)mentioning
confidence: 99%
“…True unstimulated and stimulated salivary hypofunction is consistent with the diagnosis of SS 2 , while evidence of normal flow in individuals who report subjective feelings of xerostomia is more consistent with BMS 146148 . However, it is important to be cognizant of the fact that these findings are not absolute; a minority of SS patients do not lose salivary flow and reduced unstimulated flow may be observed in BMS patients 2, 149151 . As a corollary to salivary production, patients should be questioned regarding their history of dental restorations and missing teeth, with particular emphasis on recent caries.…”
Section: Key Features To Distinguish Ss From Bmsmentioning
confidence: 99%